2009
DOI: 10.1016/j.juro.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Neutrophil Gelatinase Associated Lipocalin Levels in a Rat Model of Upper Urinary Tract Infection

Abstract: Urinary NGAL may be a potential noninvasive diagnostic biomarker of renal scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…Further, we observed that plasma NGAL levels could differentiate APN from a lower UTI and predict the treatment response of pediatric UTIs. In accordance with our findings, renal NGAL mRNA and protein levels have been shown to increase soon after bacterial injections in an experimental rat UTI model (17). Hatipoglu et al (29) showed significantly higher levels of urine matrix metalloproteinase-9/NGAL/ Cr in children with UTIs compared to those in children with contaminated urine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, we observed that plasma NGAL levels could differentiate APN from a lower UTI and predict the treatment response of pediatric UTIs. In accordance with our findings, renal NGAL mRNA and protein levels have been shown to increase soon after bacterial injections in an experimental rat UTI model (17). Hatipoglu et al (29) showed significantly higher levels of urine matrix metalloproteinase-9/NGAL/ Cr in children with UTIs compared to those in children with contaminated urine.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have also shown a possible association between increased NGAL levels and UTIs. Ichino et al (17) demonstrated experimentally that uNGAL levels in rats increased in both the early and extensive fibrosis stages of pyelonephritis, suggesting that uNGAL might also be useful as a marker of APN and renal scarring in humans. Indeed, we, and other investigators, have demonstrated that uNGAL can be a useful predictor for detecting UTIs in children (1,18).…”
mentioning
confidence: 99%
“…It has been demonstrated that NGAL is released by activated neutrophils of the infected host and prevents bacterial iron uptake consuming the ambient iron and thus reduce bacterial growth [5,6]. Recent studies revealed that uNGAL is increased in acute kidney injury (AKI) induced by nephrotoxins or ischemia, and it has been speculated that NGAL expression was induced in order to contribute to tissue regeneration after kidney damage [10,13]. Similarly, expression of NGAL increases as a part of the immune response to remove bacteria in the early stage of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Serum level of NGAL has been measured in human studies, and it has been reported that serum NGAL level is a useful marker to distinguish acute bacterial from viral infection in newborns, children, and adults [7][8][9]. Recently, Ichino et al [10] constituted an experimental pyelonephritis in rats and established that urine level of NGAL in rats increased in the early stage of UTI, suggesting that urine NGAL (uNGAL) might be used to predict UTI in humans as well.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have suggested that NGAL could discriminate the severity of infection in children, in kidney grafts and in a mouse model [4][5][6]. Therefore, in January-December 2011, we obtained a urine sample for NGAL in 50 patients (46 females and 4 males) hospitalized in our setting who underwent MR within 1 week from hospitalization for clinical suspicion of APN.…”
mentioning
confidence: 99%